2021
DOI: 10.1021/acs.jafc.1c02388
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Carboxylic Function on the Degradation of d-Galacturonic Acid and Its Polymers

Abstract: Past investigations have shown high browning potential during the caramelization of sugar acids in comparison to reducing sugars. However, no approaches to elucidate the chemical mechanisms have been made. Therefore, this study aims to clarify the reasons for the high browning potential by measuring the mutarotation velocity and the elimination of CO2 during the heat treatment of uronic acids. Performed polarimetric experiments show that the mutarotation velocity of d-galacturonic acid exceeds that of d-galact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…[39][40][41] Recently, pectin degradation studies revealed a complex process that includes demethoxylation, depolymerization by backbone hydrolysis, and cleavage of neutral sugar side chains. 42,43 Such processes require water molecules and, therefore, are affected by moisture content. Other depolymerization processes observed in pectins were ⊎-elimination and decarboxylation, neither of which require water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41] Recently, pectin degradation studies revealed a complex process that includes demethoxylation, depolymerization by backbone hydrolysis, and cleavage of neutral sugar side chains. 42,43 Such processes require water molecules and, therefore, are affected by moisture content. Other depolymerization processes observed in pectins were ⊎-elimination and decarboxylation, neither of which require water.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, pectin degradation studies revealed a complex process that includes demethoxylation, depolymerization by backbone hydrolysis, and cleavage of neutral sugar side chains 42,43 . Such processes require water molecules and, therefore, are affected by moisture content.…”
Section: Resultsmentioning
confidence: 99%
“…Many substances will be browning during storage (Tan et al, 2020;Fatouros et al, 2021). Browning mainly includes enzymatic and non-enzymatic two pathways (Paravisini and Peterson, 2019;Pham et al, 2020).…”
Section: Discussionmentioning
confidence: 99%